On the path-dependence of the fracture locus in ductile materials: Experiments. (1st October 2015) - Basu, Shamik; Benzerga, A. Amine
Abstract: Guided by previous theoretical analyses, an experimental program was designed to probe the path-dependence of the fracture locus in ductile materials. The material and loading conditions were chosen so that cavitation-induced failure is the basic damage mechanism. In one set of experiments, round notched specimens of different notch acuities were deformed to complete rupture and a nominal strain to fracture initiation was recorded for each specimen. In another set of experiments, sufficiently large specimens were prestrained in simple tension up to incipient necking, then round notched bars were cut out, again varying the notch acuity, and subsequently deformed to rupture. The latter experiments thus produce a step-jump in stress triaxiality, as opposed to a weakly varying triaxiality in the former. The evolution of stress triaxiality at failure locations was determined by finite-element calculations using an associated flow model and a hardening curve identified experimentally up to a strain of 2.0. The designed program enabled a comparison between the fracture loci with and without load path change. It also allowed qualitative comparisons to be made with previously published theoretical results. A theory of ductile fracture that is posited as a stress-state dependent critical fracture strain model is generally inadequate. The findings here partially illustrate the extent to which this applies.